CCR2- and CCR5-mediated macrophage infiltration contributes to glomerular endocapillary hypercellularity in antibody-induced lupus nephritis. (8th November 2021) - Zoshima, Takeshi; Baba, Tomohisa; Tanabe, Yamato; Ishida, Yuko; Nakatani, Kimihiko; Nagata, Michio; Mukaida, Naofumi; Kawano, Mitsuhiro
Abstract: Objectives: LN comprises various glomerular lesions, including endocapillary hypercellularity with macrophage infiltration. In this study, we aimed to clarify the involvement of macrophage-tropic chemokine receptors in the pathogenesis of these glomerular lesions. Methods: MRL/lpr mouse-derived monoclonal IgG3 antibody-producing hybridomas, 2B11.3 and B1, were injected intraperitoneally into BALB/c mice [wild type (WT)] to induce endocapillary hypercellularity and wire-loop lesions, respectively. The expression of chemokine and chemokine receptors was analysed by quantitative real-time PCR and IF. The roles of chemokine receptors in these lesions were evaluated using chemokine receptor-deficient mice or a selective CCR5 antagonist, maraviroc. Results: 2B11.3 caused glomerular endocapillary hypercellularity with a significant number of glomerular CD68-positive macrophages. Further, enhanced expression of CCL2, CCL3, CCR2, CCR5 and CX3CR1 was observed in the renal cortex, compared with B1 injection, which induced wire-loop lesions. In 2B11.3-induced glomerular lesions, CD68 -positive glomerular macrophages expressed CCL2, CCL3, CCR2, CCR5 and CX3CR1, while glomerular endothelial cells expressed CCL2, CCL3, CX3CL1 and CCR2. When 2B11.3 was injected, CCR2 –/– and CCR5 –/–, but not CX3CR1 –/–, mice exhibited reduced endocapillary hypercellularity, attenuated glomerular macrophage infiltration and improved serum blood urea nitrogen levels. Only CCR2 –/– mice developed wire-loop lesions. B1 injection caused wire-loop lesions in these chemokine receptor-deficient mice to a similar extent as WT. Maraviroc treatment reduced 2B11.3-induced endocapillary hypercellularity and improved serum blood urea nitrogen levels. Conclusion: CCR2 and CCR5 regulate glomerular macrophage infiltration and contribute to the development of glomerular endocapillary hypercellularity in LN. CCR5 inhibition can be a specific therapy for endocapillary hypercellularity without inducing wire-loop lesions.